Peningkatan Pengetahuan Gizi dan Pencegahan Stunting melalui Olahan Ikan Berbasis MP-ASI di Desa Way Muli Timur, Lampung Selatan - Verdini Liana; Nurbani Kalsum; Tiara Kurnia Khoerunnisa; Zukryandry Zukryandry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Stunting remains a critical public health problem in Indonesia, particularly in rural coastal areas. Way Muli Timur Village, South Lampung, experiences a relatively high prevalence of stunting due to inadequate nutritional intake and suboptimal childcare practices. This community service program aimed to improve nutritional knowledge and skills of women fisher groups (25 participants) in stunting prevention through training on diversified fish-based complementary foods (MP-ASI). The program was conducted over six months (April–October 2024) using lectures, hands-on food processing practices, and evaluation through pre-test and post-test assessments. The results showed a significant increase in participants' knowledge, with the average score rising from 37.50 before the intervention to 87.00 after the training, and all participants achieving post-test scores of ≥70. In addition to improving nutritional awareness, the program encouraged community-based entrepreneurship through the production of fish-based products such as fish nuggets and fish meatballs. Challenges related to limited facilities and market access were addressed through mentoring, digital marketing utilization, and the establishment of a Joint Business Group (KUB). This program has the potential to contribute to sustainable stunting prevention efforts and enhance the welfare of coastal communities through the utilization of local food resources.